Successful Repair of Infantile Scimitar Syndrome with Contralateral Pulmonary Vein Stenosis in an Infant - Onalan,Mehmet Akif (2021)
Abstract Infantile scimitar syndrome (SS) is a rare congenital heart disease and has high mortality. Guidelines have not been established, but surgery is indicated in symptomatic patients. Despite the various surgical approaches, outcomes continue to be disappointing. We present our surgical experience with an infantile SS patient who had stenotic pulmonary veins contralateral to the hypoplastic lung with complicated anatomy. There are few cases with this complex pathology in the literature. Moreover, our patient was the first transplant-free survivor with this complexity in the literature.